2021
DOI: 10.3390/molecules26103059
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Dependent Conformational Transitions in Molecular Dynamics Trajectories of GPCRs Revealed by a New Machine Learning Rare Event Detection Protocol

Abstract: Central among the tools and approaches used for ligand discovery and design are Molecular Dynamics (MD) simulations, which follow the dynamic changes in molecular structure in response to the environmental condition, interactions with other proteins, and the effects of ligand binding. The need for, and successes of, MD simulations in providing this type of essential information are well documented, but so are the challenges presented by the size of the resulting datasets encoding the desired information. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Furthermore, a long-standing challenge in MD has been to observe rare events that are related to the functional response of a GPCR. Plante et al used unsupervised machine learning to detect such rare events in the dynamic contact network of the 5-HT 2A receptor [ 37 ], comparing the functional impact of its native agonist, 5-HT, and the selective inverse agonist ketanserin. Their analysis method consisted of applying non-negative matrix factorization to the matrix representation of the dynamic contact network.…”
Section: Enhanced Description Of Allosteric Network Using Network Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a long-standing challenge in MD has been to observe rare events that are related to the functional response of a GPCR. Plante et al used unsupervised machine learning to detect such rare events in the dynamic contact network of the 5-HT 2A receptor [ 37 ], comparing the functional impact of its native agonist, 5-HT, and the selective inverse agonist ketanserin. Their analysis method consisted of applying non-negative matrix factorization to the matrix representation of the dynamic contact network.…”
Section: Enhanced Description Of Allosteric Network Using Network Theorymentioning
confidence: 99%
“…This process highlights key events that take place over the simulation while ignoring random noise in the contact network variations. For instance, the authors find that the serotonin-bound 5-HT 2A receptor undergoes a structural rearrangement in the ICL2, which induces an increase in the volume of the intracellular cavity—an activation-related event that is observed in crystal structures when bound to the heterotrimeric G protein [ 37 ].…”
Section: Enhanced Description Of Allosteric Network Using Network Theorymentioning
confidence: 99%
“…They also developed a rare event detection (RED) protocol to investigate ligand-dependent conformational transitions in cMD simulations of the serotonin 5-HT2AR receptor. 79 RED was able to identify rare transition events in residue contacts of the GPCR in response to binding of the agonist and inverse agonist. Another ML approach was developed to cluster MD simulations of the dopamine D3 receptor (D3R) for rationalizing the efficacy change induced by binding of four orthosteric ligands.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The X , Y , and Z coordinates of an atom in each simulation frame were converted to the red, green, and blue color values of a pixel in an image. They also developed a rare event detection (RED) protocol to investigate ligand-dependent conformational transitions in cMD simulations of the serotonin 5-HT2AR receptor . RED was able to identify rare transition events in residue contacts of the GPCR in response to binding of the agonist and inverse agonist.…”
Section: Introductionmentioning
confidence: 99%
“…Our key mechanistic finding of the connection between the movement of CHL among its binding modes in the hydrophobic pocket, and the movements of specific structural motifs of StarD4, emerged from the analysis of the very long MD trajectories with the time-resolved rare event detection algorithm RED (31). These trajectory analyses showed that the connected conformational changes at the β9 C-terminal and H4 N-terminal portions result in the opening of a gate between H4 and Ω1-loop, and a corridor between β9 and β7β8-loop.…”
Section: Discussionmentioning
confidence: 99%